Cognitive tasks as provocation methods in routine EEG: a multicentre field study. Issue 1 (30th March 2021) - Braga, Patricia; Mameniskiené, Rüta; Guaranha, Mirian; Zeissig, Eleonora Vega; Samaitienė, Rüta; Özcelik, Emel Ur; Bogacz, Alicia; Lin, Katia; Gardella, Elena; Yacubian, Elza Márcia; Baykan, Betül; Legnani, Mariana; et al.
Abstract: Objective : This study aimed to analyse the effect of neuropsychological activation methods on interictal epileptiform discharges, compared to standard activation methods, for both focal and generalized epilepsies. Methods : This was a multicentre, prospective study including 429 consecutive EEG recordings of individuals with confirmed or suspected diagnosis of epilepsy. Neuropsychological activation included reading aloud in foreign and native language, praxis and a letter cancelation task (each with a duration of three minutes). After counting interictal discharges in three‐minute time windows, activation and inhibition were assessed for each procedure, accounting for spontaneous fluctuations (95% CI) and compared to the baseline condition with eyes closed. Differences between generalized and focal epilepsies were explored. Results : Interictal epileptiform discharges were present in 59.4% of the recordings. Activation was seen during hyperventilation in 31%, in at least one neuropsychological activation method in 15.4%), during intermittent photic simulation in 13.1% and in the resting condition with eyes open in 9.9%. The most frequent single cognitive task eliciting activation was praxis (10.3%). Lasting activation responses were found in 18–25%. Significant inhibition was found in 88/98 patients with baseline interictal epileptiform discharges, and was not task‐specific. Significance : Adding a brief neuropsychological activation protocol to the standard EEG slightly increased its sensitivity in patients with either focal or generalized epilepsy. However, in unselected epilepsy patients, this effect seems only exceptionally to result in ultimate diagnostic gain, compared to standard procedures. From a diagnostic perspective, cognitive tasks should be reserved for patients with a suspicion of cognitive reflex epilepsy/seizures and probably require longer exposure times. Further research is needed to explore potential therapeutic applications of the observed inhibition of interictal epileptiform discharges by cognitive tasks in some patients.